2004
DOI: 10.1097/00005344-200412000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying the Sympathomimetic Cardiovascular Responses Elicited by γ-Hydroxybutyrate

Abstract: Gamma-hydroxybutyrate (GHB) is generally thought to be a central nervous system depressant; however, GHB also has sympathomimetic cardiovascular actions. Radio telemetry was used to record the cardiovascular responses elicited by GHB (180-1000 mg/kg IV) in conscious rats. GHB elicited increases in mean arterial pressure (MAP) (24 +/- 3 to 60 +/- 5 mm Hg) lasting from 28 +/- 8 to 227 +/- 37 minutes. GHB (560 and 1000 mg/kg IV) also elicited a prolonged tachycardic response (85 +/- 23 and 95 +/- 22 bpm). The hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Furthermore, following GHB intoxication hypotension is frequently reported 10 . However, recent results suggest that GHB has also sympathomimetic cardiovascular effects that could induce increases in blood pressure following its acute administratrion 38 . Further studies with a larger population of subjects are needed to confirm these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, following GHB intoxication hypotension is frequently reported 10 . However, recent results suggest that GHB has also sympathomimetic cardiovascular effects that could induce increases in blood pressure following its acute administratrion 38 . Further studies with a larger population of subjects are needed to confirm these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have shown that GHB and GHB precursors increase mean arterial pressure, heart rate (560–1,000 mg/kg, iv), and gastric emptying (100–300 mg/kg, ip or po) in rodents, and that these effects are mediated by GABA B receptors (Poggioli et al, 1999; Carai et al, 2002; Gerak et al, 2004; Hicks et al, 2004). Many studies, some of which are described below, have also implicated GABA B receptors as the primary mechanism mediating the hypnotic and anesthetic effects of GHB.…”
Section: Behavioral Effects Of Ghbmentioning
confidence: 99%
“…In addition to discriminative stimulus effects, GABA B receptor antagonists have also been shown to attenuate GHB-induced changes in brain activity, neurotransmitter release (Snead, 1996; Erhardt et al, 1998; Tremblay et al, 1998), mean arterial pressure, heart rate (Gerak et al, 2004; Hicks et al, 2004), gastric emptying (Carai et al, 2002), body temperature, locomotion, (Kaupmann et al, 2003; Quéva et al, 2003), catalepsy (Koek et al, 2007b), operant responding (Cook et al, 2002; Carter et al, 2004b; Goodwin et al, 2005), ataxia, and loss of righting (Carai et al, 2001; Cook et al, 2002; Carter et al, 2005b;Werawattanachai et al, 2007).…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…The decreased bioavailability of GHB following enteral administration is not surprising given the drug is most likely susceptible to first pass metabolism in the liver (13). The MAP increasing effect of parenterally administered GHB has been shown to be mediated via the activation of central GABA b receptors; however, the ability of parenterally administered GHB to elicit increases in heart rate have been attributed to the its' ability to selectively inhibit baroreceptor reflex control of heart rate via the activation of specific GHB receptors (2). Given that the intragastric administration of GHB did not elicit dose-dependent, parallel increases in heart rate at doses which increased MAP, it is possible that the enteral absorption of GHB alters the affinity of the compound for the GHB receptor without altering GHB's affinity for GABA b receptors.…”
Section: Discussionmentioning
confidence: 99%
“…An endogenous compound metabolically linked to gamma aminobutyric acid, GHB is considered a CNS depressant; however, GHB also has significant sympathomimetic cardiovascular properties when administered parenterally (2)(3)(4). Accompanying the increased recreational use of GHB has been an increase in drug-related toxicity.…”
Section: Introductionmentioning
confidence: 99%